Systematic Literature Review: The Influence of The Google Meet Platform on Student Learning - Slamet Waluyo Djati (CV. Akademi Merdeka, 2025)
The development of information technology in the industrial era 4.0 has influenced teaching and learning, especially through platforms such as Google Meet. Students face problems because their activeness and desire to learn online have decreased. The influence of the Google Meet Platform on student learning outcomes is assessed through the Systematic Literature Review (SLR) method. This study found that Google Meet increases students' activeness, motivation, and critical thinking skills. This finding is supported by previous research showing that Google Meet increases student participation directly. Although there are some constraints with access to devices and the internet, Google Meet is considered the best alternative option for online learning today